Absorption-line Observations of and CO in Sight Lines Toward the Vela and W28 Supernova Remnants - Nick Indriolo (The Astrophysical Journal, 2023)
Supernova remnants act as particle accelerators, providing the cosmic-ray protons that permeate the interstellar medium and initiate the ion–molecule reactions that drive interstellar chemistry. Enhanced fluxes of cosmic-ray protons in close proximity to supernova remnants have been inferred from observations tracing particle interactions with nearby molecular gas. Here I present observations of ${{\rm{H}}}_{3}^{+}$ and CO absorption, molecules that serve as tracers of the cosmic-ray ionization rate and gas density, respectively, in sight lines toward the W28 and Vela supernova remnants. Cosmic-ray ionization rates inferred from these observations range from about 2 to 10 times the average value in Galactic diffuse clouds (∼3 × 10 ^−16 s ^−1 ), suggesting that the gas being probed is experiencing an elevated particle flux. While it is difficult to constrain the line-of-sight locations of the absorbing gas with respect to the supernova remnants, these results are consistent with a scenario where cosmic rays are diffusing away from the acceleration site and producing enhanced ionization rates in the surrounding medium.